2009
DOI: 10.1590/s0103-64402009000100007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of refrigeration on the surface hardness of hybrid and microfilled composite resins

Abstract: This in vitro study evaluated the Knoop hardness of the composite resins Charisma (C) and Durafill VS (D) polymerized in 3 different conditions: at room temperature (A) (23 +/- 1 degrees C); refrigerated at 4 +/- 1 degrees C and immediately photo-activated after removal from the refrigerator (0); and, refrigerated at 4 +/- 1 degrees C and photo-activated after a bench time of 15 min at room temperature (15). One hundred and twenty specimens (4 mm diameter and 2 mm depth) were made using a stainless steel mold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 16 publications
2
12
0
3
Order By: Relevance
“…Thus a slowdown in the polymerization processes take place determining the final degree of conversion; therefore less unreacted residual monomer remains free so better mechanical properties. These come in agreement with Daronch et al (17), Osternack et al (12), Jin and Kim (39). But was disagreement with Didron et al (38) and Torres et al (10) stating that the preheating composite resins have no significant effect on microhardness, who demonstrated the strong influence of composite temperature on polymerization contraction behavior of dental resin composites.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus a slowdown in the polymerization processes take place determining the final degree of conversion; therefore less unreacted residual monomer remains free so better mechanical properties. These come in agreement with Daronch et al (17), Osternack et al (12), Jin and Kim (39). But was disagreement with Didron et al (38) and Torres et al (10) stating that the preheating composite resins have no significant effect on microhardness, who demonstrated the strong influence of composite temperature on polymerization contraction behavior of dental resin composites.…”
Section: Discussionsupporting
confidence: 92%
“…The Vickers microhardness test (VHN) has been commonly used to evaluate the hardness of dental materials, as it is usually used for brittle materials and small film thickness materials. Hardness tests are the most frequently used method to evaluate the curing depth and the polymer cross-linking of dental composites (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Daronch, et al 7 (2006) had shown that the clinician should wait at least 11 minutes before using composite stored at 3.5±0.1º C. Osternack, et al 23 (2009) showed similar top surface hardness values for the groups tested at room temperature and 15 minutes after removal from the refrigerator. If the option is the use of the technique of pre-heating, this seems to restore the characteristics of the material, at least with respect to the values of sorption and solubility.…”
Section: Discussionmentioning
confidence: 99%
“…The refrigerated storage and immediate use of the material after removal from the refrigerator can cause the material to achieve low degrees of conversion and entanglement of small chains, which leads to increased sorption and solubility. The literature has recommended to keep the composite outside the refrigerator for a period of time before using it, so that it reaches room temperature 5,7,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Karena suhu panas akan menurunkan viskositas dan meningkatkan pergerakan monomer. 10 Untuk memperpanjang waktu simpan, produsen resin komposit menginstruksikan untuk menyimpan bahan tersebut pada suhu 23°-4°C jika tidak digunakan. Instruksi ini telah dilakukan oleh dokter gigi dengan menyimpan resin komposit di dalam lemari pendingin.…”
Section: Abstrakunclassified